1986
DOI: 10.1172/jci112548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the putative neutrophil-generated toxin, hypochlorous acid, on membrane permeability and transport systems of Escherichia coli.

Abstract: Titrimetric addition of hypochlorous acid (HOCI) or chloramine (NH2Cl) to suspensions of Escherichia coli decreases their ability to accumulate "C-labeled glutamine, proline, thiomethylgalactoside, and leucine in a manner that approximately coincides with loss of cell viability; quantitative differences in cellular response are observed with the two oxidants. Inhibition of j-galactosidase activity in E. coli a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 33 publications
7
42
0
Order By: Relevance
“…The interaction of peroxidases with H 2 O 2 forms hypohalous acids, which are potent oxidants known to have several cytotoxic effects on mammalian and bacterial cells. Cell membrane integrity may be violated by membrane peroxidation and the oxidation and/or decarboxylation of membrane proteins [47,48]. In the current study, serum peroxidases significantly increased in D. puntazzo exposed to E. leei at all sampling points with the highest stimulation at 40 days p.e.…”
Section: Discussionsupporting
confidence: 45%
“…The interaction of peroxidases with H 2 O 2 forms hypohalous acids, which are potent oxidants known to have several cytotoxic effects on mammalian and bacterial cells. Cell membrane integrity may be violated by membrane peroxidation and the oxidation and/or decarboxylation of membrane proteins [47,48]. In the current study, serum peroxidases significantly increased in D. puntazzo exposed to E. leei at all sampling points with the highest stimulation at 40 days p.e.…”
Section: Discussionsupporting
confidence: 45%
“…2), suggesting that E. coli cells are able to maintain membrane permeability after chlorination. These results agree with the conclusions reached by Albrich et al (1986) who concluded that the bactericidal effect of hypochlorous acid on E. coli is not linked to changes in membrane permeability.…”
Section: ------------------------------------------------------------supporting
confidence: 93%
“…To date, the antimicrobial activity of AEW has been thought to derive from hypochlorous acid (HClO), which has a low pH and a high oxidation-reduction potential (ORP) (Al-Haq et al, 2005). Some studies have also suggested that HClO, as an undissociated form of chlorine, penetrates microbial cell membranes and subsequently achieves its antimicrobial action through the oxidation of key metabolic enzymes (Albrich et al, 1986;Barrette et al, 1989;Hurst et al, 1991).…”
Section: Introductionmentioning
confidence: 99%